Generaal J.C. Smuts se bydrae tot die ontwikkeling van die Statebondsidee, 1907-1917 - Du Plessis, Lodewickus Johannes Pierre (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M.A.) -- Universiteit van Stellenbosch, 1973.